(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
The article aims to draw the attention on the national identity components existing in the primary school textbooks during the communist times. This research, investigate the means through which history, as a part from primary school curriculum, can inculcate a set of values around which the national identity is constructed. The study uses the theoretical framework established by Pierre Nora- namely the places of memory-, and the elements of the Romanian historical mythology analyzed by Lucian Boia, -that is the myths of origins, the myth of historical continuity and unity, the myth of heroism and bravery, and the myth of the fight for independence. In addition, the study shows which were the categories of the suitable national heroes who found a place in primary school textbooks, in order to become examples to follow for pupils. The paper uses concrete examples from the textbooks covering the period 1948-1989 and it constitutes a chapter form the author's BA thesis.